Pengaruh Model PBL Berbantu Video Pembelajaran Materi Pembuatan Magnet pada Kelas VI - Prihentina Arinta Dewi; Fine Refiane; Aryo Ardi Nugroho (Journal on Education, 2023)
One of the most important steps in mass production is gel production, with the aim of knowing how the product will be used in the future. Educating students is one of many methods that can be used to help people succeed in a variety of ways. Problem-Based PBL, or PBL as it is commonly called, is a teaching method that focuses on the diversity of the local population but is not taught to the general public. In this case it serves as a guide to solitude. PBL uses real, relevant, and applicable tasks or problems in the current context, or in addition to those set in the past. As a result of these findings, there is a significant relationship between the Issue Based Learning Model and the use of video media to build magnetism for class VI students. From the results of the analysis, video is one of the many Problem-Based Learning components combined with magnetic material to produce signals for several grade VI.